KIOM-79, an Inhibitor of AGEs–Protein Cross-linking, Prevents Progression of Nephropathy in Zucker Diabetic Fatty Rats. (23rd June 2011) - Kim, Young Sook; Kim, Junghyun; Kim, Chan-Sik; Sohn, Eun Jin; Lee, Yun Mi; Jeong, Il-Ha; Kim, Hyojun; Jang, Dae Sik; Kim, Jin Sook
Abstract : Advanced glycation end products (AGEs) have been implicated in the development of diabetic complications, including diabetic nephropathy. KIOM-79, an 80% ethanolic extract obtained from parched Puerariae Radix, gingered Magnolia Cortex, Glycyrrhiza Radix and Euphorbia Radix, was investigated for its effects on the development of renal disease in Zucker diabetic fatty rats, an animal model of type 2 diabetes. In vitro inhibitory effect of KIOM-79 on AGEs cross-linking was examined by enzyme-linked immunosorbent assay (ELISA). KIOM-79 (50 mg/kg/day) was given to Zucker diabetic fatty rats for 13 weeks. Body and kidney weight, blood glucose, glycated hemoglobin, urinary albumin and creatinine excretions were monitored. Kidney histopathology, collagen accumulation, fibrinogen and transforming growth factor-beta 1 (TGF- β 1) expression were also examined. KIOM-79 reduced blood glucose, kidney weight, histologic renal damage and albuminuria in Zucker diabetic fatty rats. KIOM-79 prevented glomerulosclerosis, tubular degeneration, collagen deposition and podocyte apoptosis. In the renal cortex, TGF- β 1, fibronectin mRNA and protein were significantly reduced by KIOM-79 treatment. KIOM-79 reduces AGEs accumulation in vivo, AGE–protein cross-linking and protein oxidation. KIOM-79 could be beneficial in preventing the progression of diabetic glomerularsclerosis in type 2 diabetic rats by attenuating AGEs deposition in the glomeruli.